Faktor Penghambat Persiapan Weaning pada Pasien Terpasang Ventilasi Mekanik dengan Respiratory Failure di Ruang Intensive Care Unit (ICU) - Nurazizah, Auliyaurrahmah; Mirwanti, Ristina; Prawesti, Ayu (Jurnal Keperawatan Muhammadiyah, 2024)
Respiratory failure is the failure to provide oxygen to the entire body and the exchange of gases from the atmosphere to the blood. One of the treatments carried out in patients with respiratory failure is the installation of invasive or non-invasive mechanical ventilation. Weaning is a gradual process of reducing ventilator support carried out at the end of ventilator use. The weaning process can be successful or unsuccessful. This case report aims to discuss the inhibiting factors for weaning preparation in patients with mechanical ventilation with respiratory failure in the Intensive Care Unit (ICU). The design of this study uses the case report method to report the inhibiting factors for weaning preparation in patients with mechanical ventilation with respiratory failure in the Intensive Care Unit (ICU). A patient, a 25-year-old man came to the hospital, was transferred to the ICU due to respiratory failure after urethroplasty surgery with a condition that was already intubated with an endotracheal tube and under sedation. On the 9th day of treatment in the weaning readiness monitor. Based on the results of the monitor, it was found that the patient had a history of asthma and infection so that the nurse carried out collaborative interventions so that the asthma he had was controlled and also prevented infection. In patients, it was found that there were inhibiting factors for weaning, namely comorbid diseases and infections. For the prevention of primary infection that can be done is to maintain hand and environmental hygiene.